Correction: Ten simple rules for organizing a bioinformatics training course in low- and middle-income countries. - Benjamin Moore; Patricia Carvajal-López; Paballo Abel Chauke; Marco Cristancho; Victoria Dominguez Del Angel; Selene L Fernandez-Valverde; Amel Ghouila; Piraveen Gopalasingam; Fatma Zahra Guerfali; Alice Matimba; Sarah L Morgan; Guilherme Oliveira; et al. (PLoS Computational Biology)
[This corrects the article DOI: 10.1371/journal.pcbi.1009218.].